Challenges and perspectives of the use of photovoltaic solar energy in Colombia - Christian Manuel Moreno Rocha; Celene Milanés Batista; Willian Fernando Arguello Rodríguez; Arley Jesús Fontalvo Ballesteros; José Ricardo Núñez Álvarez (Institute of Advanced Engineering and Science, 2022)
This article quantifies the development of photovoltaic solar energy in Colombia and its current development prospects. The high demand for electricity in Colombia is increasing since there is a large population, industrial, and business increase, which brings a higher energy consumption and consequently economic, social, and environmental problems. Faced with this situation, a possible solution is proposed, using solar energy, to supply the increase in demand and mitigate the problems caused by current electricity generation because Colombia has high levels of solar radiation in almost the entire territory. The objective of this research is based on the analysis of the behavior of the projects on photovoltaic solar systems presented to the mining-energy planning unit (UPME) in the last 14 years until September 30, 2020, as well such as the study of the areas with the most effective implementation of this technology and their respective radiation indices. In addition, a synthesis is made of the regulations, laws, and tax incentives that exist for the implementation of this technology and the different stages of execution of the projects approved and in performance.